Janus polylactic acid fiber membrane for cooling and preparation method thereof

Silica modified polylactic acid Janus fiber membrane prepared by electrospinning solves the problem of low infrared emissivity and sweating in radiation cooling, achieving high-efficiency radiation refrigeration and rapid sweating, suitable for Outdoor individual cooling materials.

CN119194739AActive Publication Date: 2024-12-27SHENHUA SHENDONG COAL GRP +3

Patent Information

Application Number
CN202411592757.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2024-12-27
Estimated Expiration
2044-11-08

AI Technical Summary

Technical Problem

The existing polylactic fibers have low infrared emissivity in radiation cooling, and sweating has a negative impact on thermal comfort and cooling efficiency, making it difficult to take into account high-efficiency radiation cooling and rapid sweating performance.

Method used

The polylactic acid Janus fiber membrane modified from silica is prepared by electrospinning. The inner layer is hydrophilic and the outer layer is hydrophobic. The infrared emissivity and sunlight of the fiber are improved by combining silica nanoparticles and polylactic acid. Light reflectivity and rapid moisture absorption and sweating through the wetting gradient of the fiber membrane.

Benefits of technology

It achieves efficient radiation refrigeration effect and rapid moisture absorption and sweating ability, and has good biocompatibility and degradability, and is suitable for outdoor individual cooling materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119194739A_ABST
    Figure CN119194739A_ABST
Patent Text Reader

Abstract

The invention provides a Janus polylactic acid fiber membrane for cooling and a preparation method of the Janus polylactic acid fiber membrane. The method comprises the following steps: S1, synthesizing silicon dioxide nanoparticles; s2, dissolving silicon dioxide nanoparticles, a surfactant and polylactic acid in an organic solvent to obtain an electrostatic spinning solution A; s3, uniformly dissolving polylactic acid to obtain an electrostatic spinning solution B; s4, preparing an inner layer of the Janus fiber membrane; and S5, preparing the Janus polylactic acid fiber membrane. According to the method disclosed by the invention, the introduction of the silicon dioxide nanoparticles and the spectral selective regulation and control of the fiber diameter enable the polylactic acid fiber membrane to have high infrared emissivity and high sunlight reflection capability, and the wetting gradient of the fiber membrane can be used for rapidly conveying water from the inner layer to the outer layer. The fiber membrane not only has excellent radiation refrigeration effect and rapid moisture absorption and sweat releasing capability, but also has good biocompatibility and degradability, the preparation process is simple, and the fiber membrane is an individual cooling material with wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of fully degradable individual cooling fibers, and in particular to a Janus polylactic acid fiber film for cooling and a preparation method thereof. Background Art

[0002] As global warming intensifies, outdoor workers are more likely to be exposed to high temperatures and suffer from heat-related diseases, leading to reduced labor productivity and economic losses. Although regulating the temperature of a space through ventilation and air-conditioning systems can effectively maintain human thermal comfort, this cooling method comes at the expense of energy consumption and is not available to outdoor workers. Textiles with radiative cooling properties can spontaneously reflect sunlight to reduce energy absorption and transfer heat to outer space through atmospheric windows, providing an innovative way to cool outdoor individuals.

[0003] Nanofiber structures have high porosity and can exhibit enhanced light scattering, and have received widespread attention and extensive research in the field of radiative cooling. Polylactic acid (PLA) fiber is a sustainable ecological fiber that is biocompatible and biodegradable, and has been explored for radiative cooling. However, the inherent low infrared emissivity of PLA limits its heat radiation capacity. In addition, radiative cooling fiber membranes face the negative impact of sweating on thermal comfort and cooling efficiency in practical applications. Undischarged sweat has a large specific heat capacity, which stores heat on the skin and reduces cooling efficiency. Therefore, taking into account both efficient radiative cooling performance and excellent sweat wicking performance is the key to the development of polylactic acid individual cooling fiber membranes, but existing technologies are difficult to meet both requirements. Summary of the invention

[0004] Purpose of the invention: To meet the demand for efficient individual cooling materials in high-temperature outdoor working scenarios, the present invention prepares a Janus polylactic acid cooling fiber membrane composed of a hydrophilic inner layer of polylactic acid modified with silica and a hydrophobic outer layer of polylactic acid through an electrospinning method. The fiber membrane not only has excellent radiant cooling effect and the ability to quickly absorb moisture and perspiration, but also has good biocompatibility and degradability. The preparation process is simple, and it is an individual cooling material with broad application prospects.

[0005] The present invention specifically provides a method for preparing a Janus polylactic acid fiber membrane for cooling, comprising the following steps:

[0006] Step S1, preparing silicon dioxide nanoparticles: dissolving an organic acid in a polar solvent until the mixture is uniformly mixed to obtain a solution, adding a silicon-containing compound to the solution, stirring the mixture uniformly, and then adding an alkaline regulator, placing the mixed solution in a microwave reactor, centrifuging, washing, and drying the mixture after the reaction is completed to obtain silicon dioxide nanoparticles;

[0007] Step S2, preparing an electrospinning solution A: dissolving silica nanoparticles, a surfactant and polylactic acid in an organic solvent in sequence, and stirring to obtain an electrospinning solution A;

[0008] Step S3, preparing an electrospinning solution B: dissolving polylactic acid in an organic solvent and stirring to obtain an electrospinning solution B;

[0009] Step S4, preparing the inner layer of the Janus fiber membrane: electrospinning is performed using the electrospinning solution A as a raw material to prepare the inner layer of the Janus fiber membrane;

[0010] Step S5, preparing Janus polylactic acid fiber membrane: electrospinning is performed using electrospinning solution B as raw material to deposit fibers on the surface of the Janus inner fiber membrane to prepare the outer layer of the Janus fiber membrane, and the composite fiber membrane is placed in an oven to dry to obtain the target Janus polylactic acid fiber membrane.

[0011] In step S1, the polar solvent is at least one of ethylene glycol, polyvinyl alcohol, dimethyl sulfoxide, acetone, ethanolamine, and water;

[0012] After the mixture is stirred evenly, an alkaline regulator is added to adjust the pH value to 9-11.

[0013] In step S1, the organic acid is at least one of succinic acid, maleic acid, oxalic acid and citric acid, and the concentration of the organic acid is 0.04 to 4 mol / L.

[0014] In step S1, the silicon-containing compound is at least one of tetraethyl orthosilicate, silicic acid, silicon tetrachloride, sodium silicate, methyl orthosilicate, propyl orthosilicate, silane, and siloxane.

[0015] In step S1, the volume ratio of the silicon-containing compound to the solution is 1:2 to 1:5.

[0016] In step S1, the alkaline regulator is at least one of ammonia water, sodium hydroxide, potassium hydroxide, triethanolamine, and sodium carbamate.

[0017] In step S1, the microwave reactor has an output power of 500-6000W, a reaction temperature of 80-300°C, and a reaction time of 30 seconds-15 minutes.

[0018] In step S2, the organic solvent is at least one of chloroform, acetone, ethyl acetate, dimethylformamide, ethanol, dichloromethane, and chloroform, and the concentration of polylactic acid in the organic solvent is 0.5-20wt%;

[0019] The mass ratio of the silicon dioxide nanoparticles to the polylactic acid is 1:1 to 1:100;

[0020] The surfactant is at least one of hexadecyltrimethylammonium bromide, sodium hexadecylbenzenesulfonate, polyvinyl alcohol and sodium dodecyl sulfate, and the mass ratio of the surfactant to polylactic acid is 1:2 to 1:100.

[0021] In step S3, the organic solvent is at least one of chloroform, acetone, ethyl acetate, dimethylformamide, ethanol, dichloromethane, and chloroform, and the concentration of polylactic acid in the organic solvent is 0.5 to 40 wt%;

[0022] In step S4, the electrospinning voltage is 20-40 kV, the spinning solution consumption rate is 0.5-3 mL / h, the receiving distance is 10-24 cm, the temperature is 0-40°C, the relative humidity is 30-90%, and the average diameter of the obtained polylactic acid inner layer fiber is 100-800 nm, and the fiber membrane thickness is 100-500 μm.

[0023] In step S5, the electrospinning voltage is 15-30 kV, the spinning solution consumption rate is 5-10 mL / h, the receiving distance is 10-24 cm, the temperature is 0-40°C, the relative humidity is 30-90%, and the average diameter of the obtained polylactic acid outer layer fiber is 1.2 μm-4 μm, and the fiber membrane thickness is 50-200 μm.

[0024] The present invention also provides a Janus polylactic acid fiber membrane for cooling and cooling, which is prepared by the method described above and can be used in sportswear, outdoor equipment or air-conditioning clothing. Through its high infrared emissivity and high sunlight reflection ability, it can effectively reduce the wearer's body surface temperature. At the same time, due to its good biocompatibility and degradability, it ensures safety and comfort when in contact with the skin for a long time, and promotes the concept of sustainable development. In addition, the rapid moisture absorption and perspiration characteristics of the fiber membrane can improve the comfort during exercise, adapt to various sports scenes, such as running, cycling and outdoor adventures, and greatly enhance the user's freedom of movement and comfort.

[0025] Beneficial effects: The present invention provides a Janus polylactic acid cooling fiber membrane and a preparation method thereof. The Janus polylactic acid fiber membrane consists of a polylactic acid inner layer modified with silica and a polylactic acid outer layer. The introduction of silica nanoparticles and the spectral selective regulation of the fiber diameter enable the polylactic acid fiber membrane to have high infrared emissivity and high sunlight reflection ability. The wetting gradient of the fiber membrane can quickly transport moisture from the inner layer to the outer layer. The fiber membrane not only has excellent radiation cooling effect and the ability to quickly absorb moisture and perspiration, but also has good biocompatibility and degradability. The preparation process is simple, and it is an individual cooling material with broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments, and the above and / or other advantages of the present invention will become more clear.

[0027] Figure 1 It is a flow chart of the method of the present invention.

[0028] Figure 2 This is a scanning electron microscope image of the outer layer of the Janus polylactic acid fiber membrane in Example 1.

[0029] Figure 3 This is a scanning electron microscope image of the inner layer of the Janus polylactic acid fiber membrane in Example 1. DETAILED DESCRIPTION

[0030] Example 1

[0031] like Figure 1 As shown, this embodiment provides a method for preparing a Janus polylactic acid cooling fiber membrane, comprising the following steps:

[0032] S11. Preparation of silica nanoparticles: dissolving succinic acid (succinic acid concentration is 0.04 mol / L) in ethylene glycol until mixed evenly, adding tetraethyl orthosilicate (the volume ratio of tetraethyl orthosilicate to ethylene glycol is 1:2), stirring evenly, adding ammonia water to the solution to adjust the pH value to 9, placing the mixed solution in a microwave reactor (the output power of the microwave reactor is 700 W, the reaction temperature is 80° C., and the reaction time is 15 minutes), centrifuging after the reaction, washing, and drying to obtain silica nanoparticles;

[0033] S12. Preparing electrospinning solution A: dissolving silica nanoparticles (mass ratio of silica nanoparticles to polylactic acid is 1:10), hexadecyltrimethylammonium bromide (mass ratio of hexadecyltrimethylammonium bromide to polylactic acid is 1:20) and polylactic acid (polylactic acid concentration in the solution is 10 wt%) in dichloromethane / dimethylformamide (mass ratio 7:3) successively, and stirring to obtain electrospinning solution A;

[0034] S13. Preparing electrospinning solution B: dissolving polylactic acid in dichloromethane / dimethylformamide (mass ratio 7:3) (polylactic acid concentration in the solution is 15 wt %), and stirring to obtain electrospinning solution B;

[0035] S14. Preparation of the inner layer of the Janus fiber membrane: The electrospinning solution A raw material was electrospun (voltage 20 kV, solution consumption rate 1 mL / h, receiving distance 20 cm, temperature 25 ° C, relative humidity 40%) to prepare the inner layer of the Janus fiber membrane. The average diameter of the obtained fiber was 600 nm and the thickness of the fiber membrane was 200 μm.

[0036] S15. Preparation of Janus polylactic acid fiber membrane: electrospinning solution B raw material was used for electrospinning (voltage 20 kV, solution consumption rate 5 mL / h, receiving distance 15 cm, temperature 25°C, relative humidity 40%), so that the fibers were deposited on the surface of the Janus inner fiber membrane to obtain a Janus fiber membrane outer layer with an average fiber diameter of 2.3 μm and a fiber membrane thickness of 150 μm. The composite fiber membrane was placed in an oven to dry to obtain the target Janus polylactic acid fiber membrane.

[0037] Example 2

[0038] This embodiment provides a method for preparing a Janus polylactic acid cooling fiber membrane, comprising the following steps:

[0039] S21. Preparation of silica nanoparticles: dissolving citric acid (citric acid concentration is 0.8 mol / L) in acetone / dimethyl sulfoxide (mass ratio is 5:5) until uniformly mixed, adding silicon tetrachloride (volume ratio of silicon tetrachloride to polyvinyl alcohol is 1:4), stirring uniformly, adding sodium hydroxide to the solution to adjust the pH value to 11, placing the mixed solution in a microwave reactor (microwave reactor output power is 6000 W, reaction temperature is 150°C, reaction time is 2 minutes), centrifuging after the reaction, washing, and drying to obtain silica nanoparticles;

[0040] S22. Preparing an electrospinning solution A: dissolving silica nanoparticles (the mass ratio of silica nanoparticles to polylactic acid is 1:100), sodium dodecyl sulfate (the mass ratio of sodium dodecyl sulfate to polylactic acid is 1:80) and polylactic acid (the concentration of polylactic acid in the solution is 0.5 wt %) in dichloromethane / acetone (mass ratio 6:4) successively, and stirring to obtain an electrospinning solution A;

[0041] S23. Preparing electrospinning solution B: dissolving polylactic acid in dichloromethane / acetone (mass ratio 6:4) (polylactic acid concentration in the solution is 15 wt %), and stirring to obtain electrospinning solution B;

[0042] S24. Preparation of the inner layer of the Janus fiber membrane: electrospinning was performed using electrospinning solution A as raw material (voltage 30 kV, solution consumption rate 0.5 mL / h, receiving distance 18 cm, temperature 30° C., relative humidity 40%) to prepare the inner layer of the Janus fiber membrane, and the average diameter of the obtained fiber was 300 nm, and the thickness of the fiber membrane was 300 μm;

[0043] S25. Preparation of Janus polylactic acid fiber membrane: electrospinning solution B raw material was used for electrospinning (voltage of 15 kV, solution consumption rate of 2 mL / h, receiving distance of 15 cm, temperature of 30°C, relative humidity of 40%), so that the fibers were deposited on the surface of the Janus inner fiber membrane to obtain a Janus fiber membrane outer layer with an average fiber diameter of 1.8 μm and a fiber membrane thickness of 50 μm. The composite fiber membrane was placed in an oven to dry to obtain the target Janus polylactic acid fiber membrane.

[0044] Example 3

[0045] This embodiment provides a method for preparing a Janus polylactic acid cooling fiber membrane, comprising the following steps:

[0046] S31. Preparation of silica nanoparticles: dissolving oxalic acid (oxalic acid concentration is 4 mol / L) in water until mixed evenly, adding sodium silicate (the volume ratio of sodium silicate to polyvinyl alcohol is 1:5), stirring evenly, adding sodium hydroxide to the solution to adjust the pH value to 10, placing the mixed solution in a microwave reactor (the microwave reactor output power is 600 W, the reaction temperature is 300° C., and the reaction time is 1 minute), centrifuging after the reaction, washing, and drying to obtain silica nanoparticles;

[0047] S32. Preparing an electrospinning solution A: dissolving silica nanoparticles (the mass ratio of silica nanoparticles to polylactic acid is 1:1), hexadecyltrimethylammonium bromide (the mass ratio of hexadecyltrimethylammonium bromide to polylactic acid is 1:2) and polylactic acid in dichloromethane (the concentration of polylactic acid in the solution is 15 wt %), and stirring to obtain an electrospinning solution A;

[0048] S33. Preparation of electrospinning solution B: dissolving polylactic acid in dichloromethane (polylactic acid concentration in the solution is 40 wt%), and stirring to obtain electrospinning solution B;

[0049] S34. Preparation of the inner layer of the Janus fiber membrane: electrospinning was performed using electrospinning solution A as raw material (voltage 20 kV, solution consumption rate 2.5 mL / h, receiving distance 18 cm, temperature 24 ° C, relative humidity 45%) to prepare the inner layer of the Janus fiber membrane, and the average fiber diameter was 750 nm, and the fiber membrane thickness was 150 μm;

[0050] S35. Preparation of Janus polylactic acid fiber membrane: electrospinning was performed with electrospinning solution B as raw material (voltage 18 kV, solution consumption rate 8 mL / h, receiving distance 20 cm, temperature 24°C, relative humidity 45%) to deposit the fibers on the surface of the Janus inner fiber membrane to obtain a Janus fiber membrane outer layer with an average fiber diameter of 3.5 μm and a fiber membrane thickness of 200 μm. The composite fiber membrane was placed in an oven to dry to obtain the target Janus polylactic acid fiber membrane.

[0051] Comparative Example 1 (polylactic acid fiber membrane without modification of silicon dioxide nanoparticles)

[0052] The polylactic acid cooling fiber membrane was prepared basically by the method of Example 1. The difference is that in this example, no silica nanoparticles were added when preparing the electrospinning solution A. Specifically, hexadecyltrimethylammonium bromide (the mass ratio of hexadecyltrimethylammonium bromide and polylactic acid is 1:20) and polylactic acid (the concentration of polylactic acid in the solution is 10wt%) were successively dissolved in dichloromethane / dimethylformamide (mass ratio 7:3), and stirred evenly to obtain an electrospinning solution A; polylactic acid was dissolved in dichloromethane / dimethylformamide (mass ratio 7:3) (the concentration of polylactic acid in the solution is 15wt%), and stirred evenly to obtain an electrospinning solution B; electrospinning was carried out using the electrospinning solution A raw material (voltage 20kV, solution consumption rate 1mL / h, receiving distance 20cm, temperature 25 ℃, relative humidity 40%), to prepare the inner layer of Janus fiber membrane, the average fiber diameter of the obtained fiber is 480nm, and the fiber membrane thickness is 200μm; electrospinning solution B raw material is used for electrospinning voltage 20kV, solution consumption rate 5mL / h, receiving distance 15cm, temperature 25 ℃, relative humidity 40%), the fibers are deposited on the surface of the Janus inner fiber membrane, and the outer layer of Janus fiber membrane with an average fiber diameter of 2.3μm and a fiber membrane thickness of 150μm is obtained; the composite fiber membrane is placed in an oven to dry to obtain a polylactic acid fiber membrane without silica nanoparticle modification.

[0053] Comparative Example 2 (polylactic acid fiber membrane with single diameter distribution)

[0054] The polylactic acid cooling fiber membrane was prepared by basically adopting the method of Example 3. The difference is that in this example, the diameter of the outer fiber membrane is kept consistent with the diameter of the inner fiber by controlling the spinning parameters. Specifically, oxalic acid (oxalic acid concentration is 4 mol / L) is dissolved in water until mixed evenly, silicon tetrachloride (the volume ratio of silicon tetrachloride to polyvinyl alcohol is 1:5) is added, and after stirring evenly, sodium hydroxide is added to the solution to adjust the pH value to 10, and the mixed solution is placed in a microwave reactor (the output power of the microwave reactor is 600 W, the reaction temperature is 300°C, and the reaction time is 1 minute). After the reaction is completed, centrifugation, washing, and drying are performed to obtain silica nanoparticles; silica nanoparticles (the mass ratio of silica nanoparticles to polylactic acid is 1:1), hexadecyltrimethylammonium bromide (the mass ratio of hexadecyltrimethylammonium bromide to polylactic acid is 1:2) and polylactic acid are successively dissolved in dichloromethane (the concentration of polylactic acid in the solution is 15wt%), and stirred evenly to obtain electrospinning solution A; polylactic acid is dissolved in dichloromethane (polylactic acid) The invention relates to a method for preparing a Janus fiber membrane inner layer by electrospinning a raw material of the polylactic acid having an acid concentration of 15 wt % in the solution, and stirring the raw material to obtain an electrospinning solution B; the electrospinning solution A is used for electrospinning (voltage 20 kV, solution consumption rate 2.5 mL / h, receiving distance 18 cm, temperature 24° C., relative humidity 45%) to prepare the Janus fiber membrane inner layer, and the obtained fiber has an average diameter of 750 nm and a fiber membrane thickness of 150 μm; the electrospinning solution B is used for electrospinning (voltage 20 kV, solution consumption rate 2.5 mL / h, receiving distance 18 cm, temperature 24° C., relative humidity 45%) to deposit the fiber on the surface of the Janus inner fiber membrane to obtain a fiber membrane outer layer with an average fiber diameter of 750 nm and a fiber membrane thickness of 200 μm, and the composite fiber membrane is placed in an oven to dry to obtain a polylactic acid fiber membrane with a single diameter distribution.

[0055] Comparative Example 3 (polylactic acid fiber film without adding surfactant)

[0056] The polylactic acid cooling fiber membrane was prepared by basically adopting the method of Example 2. The difference is that no surfactant was added when preparing the electrospinning solution A in this example. Specifically, citric acid (citric acid concentration is 0.8 mol / L) is dissolved in acetone / dimethyl sulfoxide (mass ratio is 5:5) until mixed evenly, sodium silicate (volume ratio of sodium silicate and polyvinyl alcohol is 1:4) is added, and after stirring evenly, sodium hydroxide is added to the solution to adjust the pH value to 11, and the mixed solution is placed in a microwave reactor (the output power of the microwave reactor is 6000 W, the reaction temperature is 150°C, and the reaction time is 2 minutes). After the reaction is completed, centrifugation, washing, and drying are performed to obtain silica nanoparticles; silica nanoparticles (the mass ratio of silica nanoparticles to polylactic acid is 1:100) and polylactic acid (the concentration of polylactic acid in the solution is 0.5wt%) are successively dissolved in dichloromethane / acetone (mass ratio is 6:4), and stirred evenly to obtain electrospinning solution A; polylactic acid is dissolved in dichloromethane / acetone (mass ratio is 1:100) and polylactic acid (the concentration of polylactic acid in the solution is 0.5wt%). The method comprises the following steps: electrospinning the raw material of the electrospinning solution A and the raw material of the electrospinning solution B (the concentration of the polylactic acid in the solution is 15wt%) and stirring evenly to obtain an electrospinning solution B; electrospinning the raw material of the electrospinning solution A (voltage 30kV, solution consumption rate 0.5mL / h, receiving distance 18cm, temperature 30°C, relative humidity 40%) to prepare an inner layer of the fiber membrane, and the obtained fiber has an average diameter of 310nm and a fiber membrane thickness of 300μm; electrospinning the raw material of the electrospinning solution B (voltage 15kV, solution consumption rate 2mL / h, receiving distance 15cm, temperature 30°C, relative humidity 40%) to deposit the fibers on the surface of the inner fiber membrane to obtain an outer layer of the fiber membrane with an average fiber diameter of 1.8μm and a fiber membrane thickness of 50μm, and the composite fiber membrane is placed in an oven to dry to obtain a polylactic acid fiber membrane without adding a surfactant.

[0057] Structural characterization and performance testing:

[0058] Scanning electron microscope observation: The microstructure of Janus polylactic acid cooling fiber membrane was observed by field emission scanning electron microscope (model SU8220, HITACHI). Figure 2 , Figure 3 shown).

[0059] Solar reflectivity test: The reflectivity of the fiber membrane at 300-2500 nm was measured using an ultraviolet-visible-near infrared spectrophotometer (model UV-3600, Shimadzu).

[0060] Infrared reflectivity test: The infrared reflectivity and transmittance of the fiber membrane at 8-13 μm were measured using an FTIR spectrometer (model NEXUS-670, Thermo Fisher) equipped with a diffuse gold integrating sphere (PIKE Technologies).

[0061] One-way water transfer test: 15 μL of deionized water was dropped onto the outside of the Janus fiber membrane, and the transfer time of the water drop from the outside to the inside was recorded. At least 5 different positions were tested for each group of fiber membranes, and the results were averaged.

[0062] Outdoor cooling performance test: The cooling performance of the fiber membrane was measured outdoors (11:00-13:00, August 25, 2024, Xuzhou). The simulated skin (insulating foam wrapped in aluminum foil) was heated using a silicone rubber heating plate and the temperature was maintained at 37°C. A K-type thermocouple (model YET-640X, Dickway) was used to record the temperature difference between the fiber membrane under the membrane and the exposed simulated skin.

[0063] Experimental results:

[0064] like Figure 2 As shown in Figure 1, the average diameter of the outer layer of Janus polylactic acid fiber is 600nm, and the "bumps" on the fiber surface and the "bulges" inside indicate that silica nanoparticles are introduced into the polylactic acid fiber. Figure 3 As shown, the average diameter of the inner layer of the Janus polylactic acid fiber is 2.3 μm, and the fiber surface is smooth. In Example 1, the inner and outer layers of the fiber membrane present a pore size gradient, which provides favorable conditions for the directional water transmission characteristics of the Janus polylactic acid fiber.

[0065] Table 1 compares the specific surface area, dielectric properties and filtration performance test results of the Janus polylactic acid fiber membranes obtained in the examples and comparative examples. Examples 1-3 and comparative example 2 have a higher average infrared emissivity (90.51%-95.32%), because the stretching vibration of the -Si-O-Si-bond and -Si-O-bond in the silicon dioxide nanoparticles introduced into the polylactic acid fiber greatly enhances the emission of infrared light by the fiber membrane.

[0066] Table 1

[0067]

[0068] Examples 1 to 3 and Comparative Example 3 all have high solar reflectivity (92.31%-93.76%), because the diameter of the polylactic acid fiber film (including inner fiber and outer fiber) is distributed between 0.3 and 3.2 μm, covering the entire solar band (0.3-2.5 μm), thereby producing broadband solar scattering. In addition, silica particles with a particle size distribution of 0.1 to 1.1 μm can effectively scatter sunlight. No silica particles are introduced into the polylactic acid fiber film of Comparative Example 1, and its solar reflectivity is low, at 85.01%. The inner and outer diameters of the polylactic acid fiber film of Comparative Example 2 are comparable, and the fiber film diameter distribution is narrow, resulting in its solar reflectivity of only 83.31%.

[0069] Examples 1 to 3 and Comparative Example 1 all have excellent moisture absorption and perspiration wicking capabilities, and their one-way water transport time is distributed between 15-25s, which is driven by the wettability gradient and pore size gradient between the inner and outer layers of the fiber membrane. The pore sizes of the inner and outer layers of Comparative Example 2 are comparable, and water transport is driven only by the wettability gradient, so it exhibits a slower one-way water transport time. The outer layer of the fiber membrane in Comparative Example 3 is not modified with a hydrophilic surfactant, and the fiber membrane does not have a wettability gradient, so it does not exhibit one-way water transport performance.

[0070] Examples 1 to 3 and Comparative Example 3 exhibited good radiative cooling performance (cooling temperature: 10.5-11.9°C), which was due to their high infrared emission and high solar light emissivity. Comparative Examples 1 and 2 had poor radiative cooling performance, with cooling temperatures of 6.7°C and 7.2°C, respectively.

[0071] This shows that the technical solution proposed in this embodiment enables the Janus polylactic acid cooling fiber membrane to have excellent radiation cooling effect and rapid moisture absorption and perspiration removal capabilities, which are likely due to: (1) the silica nanoparticles obtained by the microwave-assisted method are uniform in size and regular in structure, and can be well dispersed in the fibers; (2) the introduction of silica nanoparticles enhances the emission of infrared light and the scattering of visible light by the fiber membrane; (3) the diameter of the fiber membrane is widely distributed in the broadband solar spectrum, so that the polylactic acid fiber membrane produces broadband solar scattering; (4) the wettability gradient and pore size gradient between the inner fiber and the outer fiber promote the rapid directional transmission of moisture.

[0072] The present invention provides a Janus polylactic acid fiber membrane for cooling and a preparation method thereof. There are many methods and ways to implement the technical solution. The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the protection scope of the present invention. All components not specified in this embodiment can be implemented by existing technologies.

Claims

1. A method for preparing a Janus polylactic acid fiber membrane for cooling, characterized in that: The following steps are involved: Step S1, preparing silicon dioxide nanoparticles: dissolving an organic acid in a polar solvent until the mixture is uniformly mixed to obtain a solution, adding a silicon-containing compound to the solution, stirring the mixture uniformly, and then adding an alkaline regulator, placing the mixed solution in a microwave reactor, centrifuging, washing, and drying the mixture after the reaction is completed to obtain silicon dioxide nanoparticles; Step S2, preparing an electrospinning solution A: dissolving silica nanoparticles, a surfactant and polylactic acid in an organic solvent in sequence, and stirring to obtain an electrospinning solution A; Step S3, preparing an electrospinning solution B: dissolving polylactic acid in an organic solvent and stirring to obtain an electrospinning solution B; Step S4, preparing the inner layer of the Janus fiber membrane: electrospinning is performed using the electrospinning solution A as a raw material to prepare the inner layer of the Janus fiber membrane; Step S5, preparing Janus polylactic acid fiber membrane: electrospinning is performed using electrospinning solution B as raw material to deposit fibers on the surface of the Janus inner fiber membrane to prepare the outer layer of the Janus fiber membrane, and the composite fiber membrane is placed in an oven to dry to obtain the target Janus polylactic acid fiber membrane.

2. The method according to claim 1, characterized in that In step S1, the polar solvent is at least one of ethylene glycol, polyvinyl alcohol, dimethyl sulfoxide, acetone, ethanolamine, and water; After the mixture is stirred evenly, an alkaline regulator is added to adjust the pH value to 9-11.

3. The method according to claim 1, characterized in that In step S1, the organic acid is at least one of succinic acid, maleic acid, oxalic acid and citric acid, and the concentration of the organic acid is 0.04 to 4 mol / L.

4. The method according to claim 1, characterized in that: In step S1, the silicon-containing compound is at least one of tetraethyl orthosilicate, silicic acid, silicon tetrachloride, sodium silicate, methyl orthosilicate, propyl orthosilicate, silane, and siloxane.

5. The method according to claim 1, characterized in that In step S1, the volume ratio of the silicon-containing compound to the solution is 1:2 to 1:

5.

6. The method according to claim 1, characterized in that In step S1, the alkaline regulator is at least one of ammonia water, sodium hydroxide, potassium hydroxide, triethanolamine, and sodium carbamate.

7. The method according to claim 1, characterized in that In step S1, the microwave reactor has an output power of 500-6000W, a reaction temperature of 80-300°C, and a reaction time of 30 seconds-15 minutes.

8. The method according to claim 1, characterized in that In step S2, the organic solvent is at least one of chloroform, acetone, ethyl acetate, dimethylformamide, ethanol, dichloromethane, and chloroform, and the concentration of polylactic acid in the organic solvent is 0.5-20wt%; The mass ratio of the silicon dioxide nanoparticles to the polylactic acid is 1:1 to 1:100; The surfactant is at least one of hexadecyltrimethylammonium bromide, sodium hexadecylbenzenesulfonate, polyvinyl alcohol and sodium dodecyl sulfate, and the mass ratio of the surfactant to polylactic acid is 1:2 to 1:

100.

9. The method according to claim 1, characterized in that: In step S3, the organic solvent is at least one of chloroform, acetone, ethyl acetate, dimethylformamide, ethanol, dichloromethane, and chloroform, and the concentration of polylactic acid in the organic solvent is 0.5 to 40 wt%; In step S4, the electrospinning voltage is 20-40 kV, the spinning solution consumption rate is 0.5-3 mL / h, the receiving distance is 10-24 cm, the temperature is 0-40 ° C, the relative humidity is 30-90%, and the average diameter of the obtained polylactic acid inner layer fiber is 100-800 nm, and the fiber membrane thickness is 100-500 μm; In step S5, the electrospinning voltage is 15-30 kV, the spinning solution consumption rate is 5-10 mL / h, the receiving distance is 10-24 cm, the temperature is 0-40°C, the relative humidity is 30-90%, and the average diameter of the obtained polylactic acid outer layer fiber is 1.2 μm-4 μm, and the fiber membrane thickness is 50-200 μm.

10. A Janus polylactic acid fiber membrane for cooling, characterized in that: The method is prepared by the method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Radiation refrigeration fiber membrane and preparation method and application thereof

    CN110042564A

  • Janus fabric membrane based on polylactic acid and preparation method and application of Janus fabric membrane

    CN111926570A

  • Janus flexible composite film for intelligent radiation thermal control and preparation method

    CN113276510A

  • Degradable consumable suitable for comprehensive management of orchard and preparation method of degradable consumable

    CN115039754A

  • Intelligent thermal control composite film capable of automatically adjusting temperature and preparation method

    CN115742488A

Cited By

  • Multi-layer fiber membrane capable of adjusting heat and humidity balance of human body and manufacturing method of multi-layer fiber membrane

    CN119800610A

  • Radiation refrigeration and photo-thermal integrated Janus polylactic acid fiber membrane and preparation method thereof

    CN119956556A

  • PLA / PTFE radiation refrigeration composite film based on electrostatic spinning method as well as preparation method and application of PLA / PTFE radiation refrigeration composite film

    CN120575388A

  • Janus polylactic acid aerogel fiber capable of realizing self-adaptive cold and heat management and preparation method thereof

    CN122588717A